Natural Resources and Development Strategy after the Crisis - Brahmbhatt, Milan; Canuto, Otaviano (World Bank, Washington, DC, 2012)
Recent events have rekindled interest in the role of primary commodities in development. Was the boom in commodity prices from around 2003 through 2008 just a cyclical event, or does it suggests that prices have entered on a period of secular strength, driven by factors such as demand in big, fast growing developing countries like China? It is notable that, while commodity prices fell sharply from their peak in 2008 with the onset of the global recession, they generally remained much higher than previous recession lows, often as high as in 2005-07, a period of robust world growth. Furthermore, prices have also rebounded smartly over the course of 2009. If a period of sustained commodity strength is imminent, what are the implications for development policies? Development economists have long debated the problems associated with the traditionally high specialization in production and export of primary commodities of most developing countries. Many argue that dependence on primary commodities has proved to be a poisoned chalice or curse for development, which, given this view, necessarily entails structural change and rapid industrialization. Others, however, suggest that sustained high commodity prices could reduce the relevance of an industrialization-focused development strategy for commodity-dependent, low-income countries (LICs). In this note authors briefly review four questions: how dependent are developing countries on primary commodity exports? What is the outlook for primary commodity prices? Is there a natural resource "curse" (or blessing)? What policies can help poor countries best manage commodity resources for long-run development?